Discrete Cutaneous Feedback for Reducing Dimensions of Wearable Haptic Devices - Leonardis, Daniele; Gabardi, Massimiliano; Barsotti, Michele; Frisoli, Antonio (Frontiers in Virtual Reality, 2022)
In this paper we explore alternative cutaneous haptic feedback for rendering modulation of the grasping force. The aim is to reduce power requirements, and in turn dimensions of the actuators, in wearable devices applied to virtual or teleoperated manipulation. This is critical in certain rehabilitation or training scenarios where haptics should not interfere with dexterity of the user. In the study we experimented a discrete, pulsed cutaneous force feedback, and compared it with conventional continuous proportional feedback, in a virtual pick and place task. We made use of wearable thimbles based on voice coil actuators in order to provide a high-quality, low-noise haptic feedback to the participants. Evaluation was performed on the basis of both objective measurements of task performance (measured virtual forces and correct ratio) and a questionnaire evaluating participants' preferences for the different feedback conditions. On the basis of the obtained results, we discuss in the paper the possibility of providing high-frequency, discretized cutaneous feedback only, driven by modulation of the grasping force. The opportunity is to reduce volume and mass of the actuators, and also to consider alternative design solutions, due to the different requirements in terms of static and high frequency components of the output force.